Model for rapidly predicting peak intensity of MICP improved construction waste, model construction method and prediction method

By establishing a model for predicting the peak intensity of MICP improved building waste, the problem of difficulty in predicting peak intensity in the prior art is solved, and efficient and economical performance evaluation of building waste is achieved, which promotes its in-engineering engineering. application.

CN119442679AActive Publication Date: 2025-02-14CHANGSHA UNIVERSITY

Patent Information

Application Number
CN202411562871.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-02-14
Estimated Expiration
2044-11-04

AI Technical Summary

Technical Problem

The prior art is difficult to quickly and accurately predict the peak intensity of MICP improved construction waste, resulting in limited engineering applications.

Method used

A model was established to extract model parameters through static triaxial tests and data analysis, and to construct formulas to quickly predict the peak intensity of MICP improved construction waste.

Benefits of technology

It significantly shortens the performance evaluation time of construction waste, reduces laboratory testing needs and costs, and improves the efficiency and economic benefits of engineering applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119442679A_ABST
    Figure CN119442679A_ABST
Patent Text Reader

Abstract

The invention relates to a model for rapidly predicting the peak intensity of MICP improved construction waste, a model construction method and a prediction method. According to the model constructed by the invention, the performance evaluation time of the construction waste can be remarkably shortened, so that an engineering project can enter a construction stage more quickly. According to the efficient evaluation means, the labor and material resource investment in the test process is reduced while the test requirements of a laboratory are reduced, so that the overall engineering cost is reduced, and the economic benefits are improved. The method provided by the invention is especially suitable for the condition with limited field conditions. The simplicity not only improves the flexibility of evaluation, but also can adjust parameters in time in actual construction, and ensures the optimal effect of MICP improvement.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of recycling of waste building materials, and relates to a model for quickly predicting the peak intensity of MICP-modified building waste, a model construction method and a prediction method. Background Art

[0002] With the rapid advancement of global urbanization, the scale of the construction industry is growing day by day, and it also brings a large amount of construction waste. The random stacking of these construction wastes not only occupies a large amount of land resources, but also pollutes the environment. Therefore, how to efficiently treat and utilize these construction wastes has become an important issue that needs to be urgently solved in the field of civil engineering. The reuse of construction waste can not only alleviate the problem of resource shortage, but also reduce the pressure on the environment, and has significant social and economic benefits. In this context, how to improve the mechanical properties of construction waste through effective technical means to achieve its wide application in engineering has become one of the hot research topics.

[0003] Microbial Induced Calcium carbonate Precipitation (MICP) technology, as an emerging biotechnology, has shown great potential in the field of civil engineering material improvement. MICP technology uses the biochemical reaction of microorganisms to generate calcium carbonate deposits, thereby forming a solid bond between particles and improving the strength and durability of the material. Compared with traditional improvement methods, such as chemical curing agents or mechanical reinforcement methods, MICP technology has the advantages of being green, environmentally friendly, low-cost, and does not produce secondary pollution. Therefore, it is regarded as a material improvement technology with sustainable development prospects. In recent years, MICP technology has been applied to soil reinforcement, crack repair, etc., and has shown good results.

[0004] Construction waste has complex composition and uneven physical properties, and its mechanical properties are usually difficult to meet the needs of direct engineering applications. Traditional construction waste improvement technologies often have problems such as being harmful to the environment, high energy consumption, and high costs, and the introduction of MICP technology provides a new idea for solving these problems. Through MICP technology, the sedimentation reaction of microorganisms can be used to generate calcium carbonate inside construction waste, making the particles more tightly bound, thereby significantly improving the strength and stability of construction waste. However, due to the complexity of the composition of construction waste, the effect of MICP improvement is affected by many factors, including the type of microorganisms, the composition of the nutrient solution, the reaction conditions, etc. Therefore, before large-scale application, the effect of MICP technology on improving construction waste must be comprehensively evaluated.

[0005] Peak strength, as an important indicator to measure the mechanical properties of materials, is directly related to the feasibility of engineering applications of improved construction waste. Traditional peak strength tests need to be completed through laboratory triaxial tests, which are usually time-consuming and costly, and are not conducive to rapid decision-making in engineering. The diversity and heterogeneity of the composition of construction waste further increase the complexity and uncertainty of experimental measurements. Therefore, establishing a method that can quickly and accurately predict the peak strength of construction waste after MICP improvement is of great significance to promote its application in practical engineering. Summary of the invention

[0006] To solve the above problems, the present invention provides a model for quickly predicting the peak intensity of MICP-modified construction waste, the model is:

[0007]

[0008] Where: k1, k2, a1, a2, a3, b1, b2, b3, c1, c2 are model parameters, σ3 is the confining pressure, R g / s is the stone-sand ratio, C Ca 2+ The calcium ion concentration of MICP-modified construction waste, D m is the number of maintenance days, and e is a mathematical constant.

[0009] The above model parameters k1, k2, a1, a2, a3, b1, b2, b3, c1, and c2 are obtained from static triaxial tests.

[0010] This application also provides a method for constructing the above model, the specific steps are as follows:

[0011] (1) Using crushed construction waste particles to prepare solid waste samples of different grades and conducting compaction tests on the samples to obtain the optimal moisture content and maximum dry density of the samples;

[0012] (2) Add equal volumes of MICP improvement reaction solutions of different concentrations to different samples and mix thoroughly;

[0013] The reaction liquid is composed of bacterial liquid and cementing liquid, and the cementing liquid is composed of calcium chloride and urea;

[0014] (3) The fully mixed sample is formed into a cylindrical sample and compacted, and then cured under different time conditions;

[0015] (4) Static triaxial test

[0016] The cured samples were subjected to static triaxial tests under different confining pressures σ3;

[0017] The peak strength of the sample under different conditions can be calculated by analyzing the stress-strain curve;

[0018] (5) According to the different conditions (R g / s , C Ca 2+ , D m The peak intensity data under σ3) are horizontally shifted relative to σ3, thus obtaining the model formula:

[0019]

[0020] Where: k1, k2, a1, a2, a3, b1, b2, b3, c1, c2 are model parameters, σ3 is the confining pressure, R g / s is the stone-sand ratio, C Ca 2+ The calcium ion concentration of MICP-modified construction waste, D m is the number of maintenance days, and e is a mathematical constant.

[0021] Based on the above scheme, in step (1), the R g / s The values ​​are 1.0, 1.5, 2, 2.5 and 3.

[0022] Based on the above scheme, in step (2), C in the reaction solution Ca 2+ Set to 0mol / L, 0.5mol / L, 1mol / L and 2mol / L.

[0023] Based on the above scheme, in step (3), the curing time D m Set to 0, 1, 3, 6, 10 days.

[0024] On the basis of the above scheme, in step (4), σ3 in the test is set to 50 kPa, 100 kPa, and 150 kPa, and the shear rate is 0.5% / min.

[0025] Based on the above scheme, the bacteria in the bacterial solution of the reaction solution in step (2) is Bacillus pasteurii, and the bacterial solution concentration is OD 600 =3.0.

[0026] The beneficial effects of the present invention are:

[0027] (1) Improve construction efficiency and reduce costs: The model constructed by the method of this application can significantly shorten the performance evaluation time of construction waste, allowing the project to enter the construction phase more quickly. This efficient evaluation method reduces the demand for laboratory testing while reducing the human and material input during the testing process, thereby reducing the overall project cost and improving economic benefits.

[0028] (2) Simplicity of field application: Compared with the traditional peak strength test which usually requires professional equipment and complicated experimental steps, the rapid prediction method proposed in the present invention can simplify the process through the model. It only needs to input the corresponding Rg / s value, C Ca 2+ The corresponding peak intensity can be quickly estimated based on the concentration, Dm and σ3, which is especially suitable for situations where on-site conditions are limited. This simplicity not only improves the flexibility of the evaluation, but also enables timely adjustment of parameters in actual construction to ensure the best effect of MICP improvement.

[0029] (3) Optimizing the improvement effect: The rapid prediction method proposed in the present invention can also be used to guide the optimization of MICP technology, helping to determine key parameters such as calcium ion concentration and curing days, so as to obtain the best improvement effect under different construction waste conditions. This targeted parameter adjustment helps to improve the final mechanical properties of construction waste and ensure its reliability and safety in engineering applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0031] Figure 1 This is a schematic diagram of construction waste materials used in Example 2 of the present application;

[0032] Figure 2 This is a flow chart of the quantitative analysis method for the shape of construction waste particles in Example 2 of the present application;

[0033] Figure 3 The shape classification results of different components of construction waste in Example 2 of the present application, wherein: (a) stone; (b) mortar block; (c) brick;

[0034] Figure 4 The different R in Example 2 of this application g / s The screening test results and compaction test results of construction waste under the following conditions; where: (a) screening test results; (b) compaction test results;

[0035] Figure 5 This is a diagram of the triaxial test device in Example 2 of the present application;

[0036] Figure 6 The different R in Example 2 of this application g / sEffect on strength properties; where: (a) stress-strain curve; (b) peak strength;

[0037] Figure 7 For different C in Example 2 of this application Ca 2+ Effect on strength properties; where: (a) stress-strain curve; (b) peak strength;

[0038] Figure 8 D in Example 2 of this application m Effect on strength properties; where: (a) stress-strain curve; (b) peak strength;

[0039] Fig. 9 The influence of different σ3 on the strength characteristics in Example 2 of the present application; wherein: (a) stress-strain curve; (b) peak strength;

[0040] Fig.10 This is a robustness verification diagram in Example 2 of the present application; DETAILED DESCRIPTION

[0041] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0042] Example 1

[0043] The present application provides a method for constructing a model for rapidly predicting the peak intensity of MICP-modified construction waste, and the specific steps are as follows:

[0044] (1) Use crushed construction waste particles to prepare solid waste samples of different grades and conduct compaction tests on the samples to obtain the optimal moisture content and maximum dry density of the samples; R g / s Values ​​can be set to 1.0, 1.5, 2, 2.5, and 3 respectively.

[0045] (2) adding equal volumes of reaction solutions of different concentrations for MICP improvement to different samples for thorough mixing; the reaction solution is composed of bacterial solution and a binder solution, and the binder solution is composed of calcium chloride and urea;

[0046] C in the reaction solution Ca 2+ The concentration of the bacterial solution is OD 600 =3.0.

[0047] (3) The fully mixed sample is made into a cylindrical sample and compacted, and then cured under different time conditions; the curing time D m Set to 0, 1, 3, 6, 10 days.

[0048] (4) Static triaxial test

[0049] The cured samples were subjected to static triaxial tests under different confining pressures σ3; the σ3 in the tests was set to 50 kPa, 100 kPa, and 150 kPa, and the shear rate was 0.5% / min.

[0050] The peak strength of the sample under different conditions can be calculated by analyzing the stress-strain curve;

[0051] (5) According to the different conditions (R g / s , C Ca 2+ , D m The peak intensity data under σ3) are horizontally shifted relative to σ3, thus obtaining the model formula:

[0052]

[0053] Where: k1, k2, a1, a2, a3, b1, b2, b3, c1, c2 are model parameters, σ3 is the confining pressure, R g / s is the stone-sand ratio, C Ca 2+ The calcium ion concentration of MICP-modified construction waste, D m is the number of maintenance days, and e is a mathematical constant.

[0054] Example 2

[0055] Based on the method in Example 1, the present application provides a specific method for constructing a model for rapidly predicting the peak intensity of MICP-modified construction waste.

[0056] Step a: Experimental materials and protocols

[0057] 2.1 Test materials

[0058] The construction waste materials selected in this example (after crushing and screening) come from the demolition waste of a construction site in Changsha. Within the particle size range of 0 to 20 mm, the mass proportions of each component are as follows: 77.3% of stone, 12.8% of mortar block, 7.5% of brick, and 2.4% of other impurities (such as tiles, glass, etc.). Figure 1 shown.

[0059] The geometric characteristics of particles (such as sphericity, flatness, aspect ratio, etc.) have a significant impact on the skeleton structure and strength characteristics of the filler (such as peak strength, internal friction angle, cohesion, etc.). Based on this, this example performed three-dimensional blue light scanning and reconstruction on a total of 450 particles of stone, mortar blocks, and bricks (including 150 stones, 150 mortar blocks, and 150 bricks). Figure 2 The aspect ratio (EI), flatness (FI) and sphericity (S) of each particle were calculated. P ) and other shape indicators. Then, the particle shapes were classified by T.Zingg bivariate classification method. The results are shown in Figure 3 As shown. Figure 3 It can be seen that most of the stone, mortar and brick particles are block-shaped or disc-shaped. Among them, the sphericity values ​​of stone and brick are mainly distributed between 0.5 and 1, while the sphericity values ​​of mortar are concentrated between 0.67 and 1.

[0060] The basic physical performance indicators of construction waste are shown in Table 1. At the same time, considering that the influence of gradation on the strength characteristics of construction waste cannot be ignored, this example introduces the stone-sand ratio (R g / s ) indicator. g / s The application of the method must meet the following conditions: (1) the boundary particle size between coarse and fine particles must be around 5 mm; (2) the grading curve can be well fitted by the Fuller function.

[0061] Among them, the R g / s The parameter can be determined by the maximum particle size D max The shape parameter n of the grading curve is calculated according to formula (1), and n can be calculated from the screening results according to the Fuller function (formula 2):

[0062]

[0063] In the formula, R g / s is the stone-sand ratio; p d The aperture is d i The cumulative pass rate corresponding to the sieve holes; d i is the sieve aperture, D max is the maximum particle size. In addition, according to the USCS classification system (ASTM 2001), gravel is the particle that passes through a 75 mm sieve and is retained on a 5 mm sieve, and the content of gravel is 1-p5; sand (s) is the particle that passes through a 5 mm sieve and is retained on a 0.075 mm sieve.

[0064] Table 1 Basic physical properties of construction waste

[0065]

[0066] Considering the "Highway Subgrade Structure Design Code" (JTGD30-2015) and the sample size limit of the triaxial test (the maximum particle size shall not exceed 1 / 5 of the sample diameter), this embodiment sieves the construction waste into different particle size groups after drying, and the maximum particle size is 20mm. Furthermore, five solid waste samples with different gradations are designed, and their R g / s The values ​​are 1.0, 1.5, 2, 2.5 and 3 respectively, and the grading curve is as follows Figure 4 (a) shows the corresponding compaction test results. Figure 4 (b) as shown.

[0067] 2.2 Preparation of reaction solution

[0068] Based on the reaction mechanism of MICP, the reaction solution consists of bacterial solution and cementing solution. Its basic reaction equation is shown in formulas (3) to (5):

[0069]

[0070] Ca 2+ +Cell—→Cell-Ca 2+ (4)

[0071] Cell-Ca 2+ +CO3 2- —→Cell-CaCO3↓ (5)

[0072] In an alkaline environment, bacteria secrete urease through metabolic activities, which can continuously hydrolyze urea to produce NH4 + and CO3 2- Since the bacterial surface has a negative charge, it can attract Ca in the surrounding medium. 2+ , and then with CO3 2- Combined to form calcium carbonate crystals with cementing effect. In this process, bacteria are not only responsible for the production of urease and the hydrolysis of urea, but also serve as the core attachment point for calcium carbonate precipitation. Therefore, cultivating a large amount of highly active bacterial liquid is a key step in the implementation of MICP technology.

[0073] There are many types of bacteria used for MICP improvement. This embodiment uses environmentally friendly and non-toxic Sporosarcina pasteurii (CGMCC 1.3687) as the bacteria. In order to activate and expand the culture of bacteria, this embodiment uses NH4-YE liquid culture medium, and the specific components are shown in Table 2. After the culture medium is prepared, it is divided into sterile containers and sterilized with high-pressure steam at 121°C for 20 minutes to ensure the sterility of the culture environment. After the culture medium is cooled to room temperature, the activated bacteria are aseptically inoculated at a ratio of 1:100.

[0074] Table 2 NH4-YE liquid culture medium components

[0075]

[0076] The inoculated bacterial solution was placed in a constant temperature shaking incubator and cultured continuously for 20 hours at 30°C and 150 r / min. After the culture was completed, the optical density (OD) of the bacterial solution was measured using a TU-1950 UV-visible spectrophotometer. 600 ) to evaluate the growth concentration of bacteria. At the same time, the urease activity of the bacterial solution was measured using a DDS-11A conductivity meter. The urease activity was calculated based on the empirical formula of Whiffin et al., and the change in conductivity was converted into the amount of urea hydrolyzed per unit time. In this embodiment, the bacterial solution concentration obtained by culture is OD 600 =3.0, and the corresponding urease activity is 15.4 μmol of urea per minute. In addition, this embodiment uses a mixed cementing liquid composed of calcium chloride (CaCl2) and urea. Among them, CaCl2 is used as a calcium source to provide the necessary Ca for the reaction. 2+ Urea not only provides a nitrogen source for bacterial metabolic activities, but also hydrolyzes to produce CO3 under the action of urease 2- , with Ca 2+ Combine to form calcium carbonate precipitate.

[0077] 2.3 Experimental plan

[0078] The experimental scheme of this embodiment can be divided into the following four parts:

[0079] (a) MICP treatment of construction waste

[0080] The compaction test results (such as Figure 4 As shown) determine different R g / s The optimal moisture content of the sample is determined, and the MICP reaction solution is prepared according to Section 2.2. Ca 2+ Set to 0mol / L, 0.5mol / L, 1mol / L and 2mol / L. Add equal volumes of the prepared reaction solution (same as the optimal water content volume) to different R g / s In the sample, stir and mix thoroughly to ensure that the microorganisms and Ca 2+ Uniform contact between particles.

[0081] (b) Sample preparation and curing

[0082] Cylindrical specimens with a diameter of 101 mm and a height of 200 mm were prepared using a standard split die, and the compaction test results (such as Figure 4 As shown) determine different R g / sThe samples were compacted to 95% of their maximum dry density. Then, to ensure the effectiveness of the MICP treatment, the samples were immediately placed in a constant temperature and humidity curing box (the curing temperature was set at 25°C) after preparation. m Effect of MICP treatment on the m The settings for increasing the backward difference are 0, 1, 3, 6, and 10 days.

[0083] (c) Static triaxial test

[0084] ① Without MICP treatment (C Ca 2+ =0mol / L, D m =0) of construction waste samples, at σ3 = 100 kPa and different R g / s The stress-strain curves and peak strength under (1.0, 1.5, 2, 2.5, 3) conditions are shown in Figure 6 shown.

[0085] ② Different C Ca 2+ (0mol / L, 0.5mol / L, 1mol / L and 2mol / L) solid waste samples, in R g / s =2.5,σ3=100kPa and D m =0,6(C Ca 2+ =0mol / L, D m =0) under the condition of stress-strain curve and peak strength as shown in Figure 7 shown.

[0086] ③ Different D m (0, 1, 3, 6, 10) solid waste samples, in R g / s =2.5,σ3=100kPa and C Ca 2+ =0,1mol / L(D m =0, C Ca 2+ =0mol / L) under the condition of stress-strain curve and peak strength as shown in Figure 8 shown.

[0087] ④R g / s =2.5 solid waste samples, at different σ3 (50kPa, 100kPa, 150kPa), C Ca 2+ =0mol / L, D m = 0 condition, the stress-strain curve and peak strength are shown in Fig. 9 shown.

[0088] The static triaxial test was carried out by using the Dynatriax100 / 14 fully automatic triaxial test system of Changsha University of Science and Technology (such as Figure 5 As shown). In order to simulate the stress state of roadbed filler at different depths and stress conditions as much as possible, σ3 in the static triaxial (UU) test is set to 50kPa, 100kPa, and 150kPa, and the shear rate is 0.5% / min. On this basis, the peak strength, internal friction angle, and cohesion of the sample under different conditions can be calculated by analyzing the stress-strain curve. Among them, for the strain hardening curve, the axial stress corresponding to its 15% axial strain is selected as the peak strength; for the strain softening curve, the axial stress corresponding to the peak value of the curve is selected as the peak strength; the corresponding internal friction angle and cohesion are obtained by combining the peak strength and the Mohr-Coulomb failure criterion.

[0089] The specific test plan is shown in Table 3.

[0090] Table 3 Triaxial test scheme

[0091]

[0092] Step b: Triaxial test results and analysis

[0093] 3.1 Effect of different stone-sand ratios on strength characteristics

[0094] Without MICP treatment (C Ca 2+ =0mol / L, D m =0) of construction waste samples, at σ3 = 100 kPa and different R g / s The stress-strain curves and peak strength under (1.0, 1.5, 2, 2.5, 3) conditions are shown in Figure 6 As shown in Figure 2, the peak intensity increases with R g / s The improvement of R g / s =1, its peak intensity is 173.4 kPa. g / s =2.5, its peak intensity reaches a maximum value of 389.4 kPa, and when R g / s When =3, its peak intensity drops to 356.3kPa.

[0095] This is due to the fact that at lower R g / s (such as 1, 1.5) the internal structure of the sample is loose, the friction between particles is weak, and the peak strength is low. g / s As the skeletal effect between the stone particles increases, the structural compactness and stability of the sample gradually increase, which is reflected in the macroscopic aspect as R g / s =2.5 is the best R g / s However, when R g / sWhen R is too high (such as 3), although the skeleton effect between the stone particles is still strengthened, the bonding between the particles is also greatly weakened, thereby reducing the overall bearing capacity of the sample. In addition, it can be seen from the shape of the stress-strain curve that the strain softening effect increases with R g / s The stress drop after the peak strength increases with the increase of R g / s Under these conditions, the specimen is more likely to experience a significant decrease in overall bearing capacity after local failure.

[0096] Reasonable choice of R g / s The strength characteristics of construction waste roadbed filling are of great significance. Therefore, in actual engineering, the optimal R g / s It is very necessary.

[0097] 3.2 Effect of different calcium ion concentrations on strength characteristics

[0098] Different C Ca 2+ (0mol / L, 0.5mol / L, 1mol / L and 2mol / L) solid waste samples, in R g / s =2.5,σ3=100kPa and D m =0,6(C Ca 2+ =0mol / L, D m =0) under the condition of stress-strain curve and peak strength as shown in Figure 7 In general, each C Ca 2+ The stress-strain curves under the conditions showed similar trends: the stress increased rapidly in the initial stage and gradually decreased after reaching the peak. Ca 2+ The specific shape of the curve and the change of peak intensity show significant differences.

[0099] First, in C Ca 2+ =0mol / L, the initial rising rate of the soil sample is relatively slow, the peak strength is 389.4kPa, and then the stress shows a steady downward trend, indicating that the internal structure of the soil is loose, the bonding force between particles is weak, and the bearing capacity is limited. Then, with the increase of C Ca 2+ =0.5mol / L, the initial stress rise rate of the soil sample accelerated, and the peak strength increased to 639.2kPa, indicating that the appropriate amount of Ca 2+ It can enhance the bonding force between soil particles and improve its bearing capacity. At the same time, the stress decreases slowly after the peak value, showing a certain toughness. Ca 2+=1mol / L, the initial rise rate of the soil sample further increased, and the peak strength reached nearly 799.6kPa, which was the maximum value under all test conditions. However, the stress dropped rapidly after the peak strength, showing obvious brittle failure characteristics. This shows that Ca 2+ At this concentration, the bearing capacity of the soil is greatly enhanced, but at the same time, the toughness and post-failure bearing capacity of the soil are also reduced. Ca 2+ =2mol / L, the peak intensity slightly dropped to 693.1kPa, but still higher than C Ca 2+ =0.5mol / L. This is because Ca 2+ It can react with the mineral particles in the sample to form a stable cementing layer, significantly enhancing the bonding force between particles, thereby improving the strength of the sample. Ca 2+ =0.5, 1 mol / L, the peak strength of the sample increased significantly. At the same time, an appropriate amount of calcium ions can improve the arrangement and mutual interlocking of soil particles, increase the friction between particles, and improve the strength characteristics of the soil. However, too high C Ca 2+ (such as 2mol / L) will cause the soil to become more brittle and its bearing capacity to decrease significantly.

[0100] 3.3 Effect of different curing days on strength characteristics

[0101] Different D m (0, 1, 3, 6, 10) solid waste samples, in R g / s =2.5,σ3=100kPa and C Ca 2+ =0,1mol / L(D m =0, C Ca 2+ =0mol / L) under the condition of stress-strain curve and peak strength as shown in Figure 8 As shown. In general, the stress-strain curves under various curing conditions show similar trends: the stress rises rapidly with the strain in the initial stage, then tends to be flat, and gradually decreases after reaching the peak. This shows that the soil sample experienced an elastic deformation stage at the beginning of loading, then entered the plastic deformation stage as the stress increased, and finally the stress decreased due to the destruction of the internal structure.

[0102] Specifically, under no maintenance conditions (D m =0), the peak strength of the soil sample is 389.4 kPa, indicating that the bonding between the internal particles of the soil is weak and the overall structure is loose, resulting in a low bearing capacity. m The peak intensity increases significantly. m=1, the peak strength increases to 620.1 kPa, indicating that calcium carbonate precipitation begins to form a preliminary cementation effect between particles, enhancing the bearing capacity of the soil and the stability of the internal structure. m =3, the peak strength further increases to 697.1 kPa, indicating that the enhancement of calcium carbonate deposition significantly improves the internal bonding force of the soil, the particles are more tightly combined, the soil structure is more stable, and the bearing capacity is greatly improved.

[0103] In D m =6, the peak strength reaches 799.6 kPa, the highest value under all curing conditions, indicating that the calcium carbonate precipitation inside the soil is the most complete at this time, the bonding force and friction between particles are both at their maximum, and the bearing capacity and initial stiffness of the soil are both at their best. However, as the peak strength increases, the curve also decreases rapidly after reaching the peak value, indicating that the brittleness of the soil sample increases after failure, and the bearing capacity decreases rapidly. This may be due to the excessive cementation caused by excessive precipitation of calcium carbonate, which makes it impossible for the soil to maintain overall stability after local structural failure.

[0104] When D m =10, the peak strength further increased to 817.7 kPa, but the downward trend of the curve was steeper, showing a more obvious strain softening effect. This shows that although the increase in the amount of calcium carbonate precipitation has improved the strength of the soil, the excessively long curing time may lead to an increase in the inhomogeneity of the internal structure of the soil, thereby reducing the stability and toughness of the overall structure. Therefore, although the strength of the soil has increased in the short term, the bearing capacity has rapidly decreased after failure, showing a strong brittle characteristic.

[0105] The influence mechanism of MICP curing days on the strength characteristics of construction waste is mainly reflected in the following three aspects: First, with the increase of D m With the increase of curing days, the microbial-induced calcium carbonate precipitation gradually acts as a cementing material between particles, effectively enhancing the bonding force and friction of particles inside the soil. During the 3 to 6 days of curing, the calcium carbonate precipitation is relatively sufficient, the soil structure reaches the optimal state, and the bearing capacity is significantly improved. Secondly, when the curing days exceed 6 days, the excessive deposition of calcium carbonate may cause local inhomogeneity inside the soil, destroy the uniformity and stability of the overall structure, increase the brittleness of the soil, and accelerate the stress drop rate after the peak strength. Finally, the brittle failure characteristics of the soil become more and more obvious with the increase of curing days, especially at 6 and 10 days of curing. After reaching the peak strength, the soil structure is prone to instability and the bearing capacity decreases rapidly.

[0106] In summary, different MICP curing days have a significant impact on the mechanical properties of the soil. Appropriate curing time (such as 3 to 6 days) can effectively improve the bearing capacity and initial stiffness of the soil, making it have better bearing capacity and structural stability. However, too long a curing time (such as 10 days) may lead to excessive deposition of calcium carbonate, increase the internal heterogeneity and brittleness of the soil, and thus reduce its overall strength and bearing capacity after failure. Therefore, in actual engineering applications, the MICP curing time should be reasonably controlled to achieve the best improvement effect of the mechanical properties of the soil.

[0107] 3.4 Effect of different confining pressures on strength characteristics

[0108] R g / s =2.5 solid waste samples, at different σ3 (50kPa, 100kPa, 150kPa), C Ca 2+ =0mol / L, D m = 0 condition, the stress-strain curve and peak strength are shown in Fig. 9 As shown. Fig. 9 It can be seen that with the increase of confining pressure, the stress-strain behavior of the soil gradually changes from strain softening to strain hardening. When σ3=50kPa, the curve shows obvious strain softening characteristics, and the peak strength is 259.6kPa. At this time, the contact between particles inside the soil is loose, the peak strength is low, and the stress gradually decreases after reaching the peak strength, indicating that the bearing capacity of the soil sample decreases during the deformation process, and it has good plastic deformation capacity. When σ3=100kPa, the curve shape transitions from strain softening to strain hardening, and the peak strength increases to 389.4kPa. At this time, the friction and bonding force between particles inside the soil are enhanced, and the structure is more compact. Although the stress decreases after the peak strength, the decrease is reduced, the strain softening effect of the soil is weakened, and the bearing capacity is maintained in a larger strain range, showing good plasticity and toughness. At σ3=150kPa, the stress-strain curve of the soil shows obvious strain hardening characteristics, and the peak strength reaches 454.3kPa. The interlocking and friction between the particles inside the soil are further enhanced, the structural stability is significantly improved, and the bearing capacity reaches the maximum value. The soil does not show obvious softening under large strain conditions, and the bearing capacity increases with the increase of strain, showing good plastic deformation ability and toughness.

[0109] Step c: Model construction and validation

[0110] The principle of the master curve translation method is explained as follows: g / s , C Ca 2+ , D mThe peak intensity data of σ3) are horizontally shifted relative to σ3 until these curves merge into a single S-shaped function that takes into account R through the shift factor function. g / s , C Ca 2+ , D m Influence of factors such as.

[0111] σ3 and S p There is a basic linear relationship, as shown in formula (C1):

[0112]

[0113] In the formula, S p is the peak intensity, k1 and k2 are model parameters, and the other meanings are the same as above.

[0114] For the convenience of calculation, the formula (C1) is transformed into a logarithmic equivalent, as shown in the formula (C2):

[0115] oeLh p =k1+k2lnσ3 (C2)

[0116] The master curve translation method is used to gradually correct different influencing factors and obtain the comprehensive consideration R g / s , C Ca 2+ , D m , and the peak intensity prediction model of σ3 is as follows:

[0117] ①R g / s Pan:

[0118] Formula C3 is composed of Formula C3-1 and Formula C3-2:

[0119] oeLh p =k1+k2(lnσ3+a1R g / s 2 +a2R g / s +a3) (C3)

[0120] in:

[0121] oeLh p =k1+k2lnσ 3-① (C3-1)

[0122] lnσ 3-① =lnσ3+a1R g / s 2 +a2R g / s +a3 (C3-2)

[0123] ②C Ca 2+ -Rg / s Pan:

[0124] Formula C4 is composed of Formula C4-1 and Formula C4-2:

[0125] oeLh p =k1+k2(lnσ3+a1R g / s 2 +a2R g / s +a3+b1C Ca2+ 2 +b2C Ca2+ +b3) (C4)

[0126] in:

[0127] oeLh p =k1+k2lnσ 3-② (C4-1)

[0128] lnσ 3-② =lnσ 3-① +b1C Ca2+ 2 +b2C Ca2+ +b3 (C4-2)

[0129] ③D m -C Ca 2+ -R g / s Pan:

[0130] Formula C5 is composed of Formula C5-1 and Formula C5-2:

[0131] oeLh p =k1+k2(lnσ3+a1R g / s 2 +a2R g / s +a3+b1C Ca2+ 2 +b2C Ca2+ +b3+c1ln(e+D m )+c2)(C5)where:

[0132] oeLh p =k1+k2lnσ 3-③ (C5-1)

[0133] lnσ 3-③ =lnσ 3-② +c1ln(e+D m )+c2 (C5-2)

[0134] In summary, we can get formula C6

[0135]

[0136] In the formula: a1, a2, a3, b1, b2, b3, c1, c2 are model parameters, and the other meanings are the same as above.

[0137] In addition, the estimated model parameters are shown in Table 4.

[0138] Table 4 Statistics of estimated model parameters

[0139]

[0140] The model parameters are given by Figure 6-Figure 9 The data was obtained by nonlinear least squares fitting (NLSF) technology in SPSS software.

[0141] In order to determine the applicability of the model constructed by the present invention, the above model formula is verified for robustness. p The measured value is the horizontal axis, S p The estimated value is used as the vertical axis to draw a robustness verification scatter plot, and the results are as follows Fig.10 As shown in Figure 2, it can be seen that most of the scattered points are concentrated around the straight line y=x, R 2 =0.98, RMSE=12.46, and the fitting effect is good. Therefore, the shear strength obtained by the model constructed in this embodiment is highly representative and meets the engineering needs.

[0142] The above description is only a preferred embodiment of the present invention and is not intended to limit the protection scope of the present invention. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention are included in the protection scope of the present invention.

Claims

1. A model for rapidly predicting the peak intensity of MICP-modified construction waste, characterized in that: The model is: Where: k1, k2, a1, a2, a3, b1, b2, b3, c1, c2 are model parameters, σ3 is the confining pressure, R g / s is the stone-sand ratio, C Ca 2+ The calcium ion concentration of MICP-modified construction waste, D m is the number of maintenance days, and e is a mathematical constant.

2. A model for rapidly predicting the peak intensity of MICP-modified construction waste, characterized in that: The model parameters k1, k2, a1, a2, a3, b1, b2, b3, c1, and c2 are obtained from static triaxial tests.

3. A method for constructing the model according to claim 1 or 2, characterized in that: The specific steps are as follows: (1) Using crushed construction waste particles to prepare solid waste samples of different grades and conducting compaction tests on the samples to obtain the optimal moisture content and maximum dry density of the samples; (2) Add equal volumes of MICP improvement reaction solutions of different concentrations to different samples and mix thoroughly; The reaction liquid is composed of bacterial liquid and cementing liquid, and the cementing liquid is composed of calcium chloride and urea; (3) The fully mixed sample is formed into a cylindrical sample and compacted, and then cured under different time conditions; (4) Static triaxial test The cured samples were subjected to static triaxial tests under different confining pressures σ3; The peak strength of the sample under different conditions can be calculated by analyzing the stress-strain curve; (5) According to the different conditions (R g / s , C Ca 2+ , D m The peak intensity data under σ3) are horizontally shifted relative to σ3, thus obtaining the model formula: Where: k1, k2, a1, a2, a3, b1, b2, b3, c1, c2 are model parameters, σ3 is the confining pressure, R g / s is the stone-sand ratio, C Ca 2+ The calcium ion concentration of MICP-modified construction waste, D m is the number of maintenance days, and e is a mathematical constant.

4. The method according to claim 3, characterized in that In step (1), the R g / s The values ​​are 1.0, 1.5, 2, 2.5 and 3.

5. The method according to claim 3, characterized in that: In step (2), C in the reaction solution Ca 2+ Set to 0mol / L, 0.5mol / L, 1mol / L and 2mol / L.

6. The method according to claim 3, characterized in that In step (3), the curing time D m Set to 0, 1, 3, 6, 10 days.

7. The method according to claim 3, characterized in that In step (4), σ3 in the test was set to 50 kPa, 100 kPa, and 150 kPa, and the shear rate was 0.5% / min.

8. The method according to claim 3, characterized in that The bacteria in the reaction solution in step (2) are Bacillus pasteurii, and the concentration of the bacteria is OD 600 =3.

0.

9. A model constructed according to the method according to any one of claims 3 to 9.

10. A method for rapidly predicting the peak intensity of MICP-modified construction waste, characterized in that: Use the model of claim 1 or 9.

Citation Information

Patent Citations

  • Humidity and stress-based construction waste roadbed filler permanent deformation estimation method

    CN112347630A

  • Method for quickly predicting critical failure stress of subgrade soil

    CN112461657A

  • Triaxial test sample preparation device for reinforcing sandy soil based on MICP technology and use method

    CN116429539A

  • Method for rapidly estimating optimal modification parameters of MICP modified subgrade soil

    CN116451458A

  • Method for rapidly estimating shear strength of MICP modified building solid waste fine material and modeling method of model

    CN116910860A

Cited By

  • Multi-scale evaluation method and system for mechanical strength of construction waste mixture for road

    CN120213611A